Teacher's code-switching and bilingual children's heritage language learning and cognitive switching flexibility. Issue 2 (30th March 2020) - SUN, He; YUSSOF, Nurul; VIJAYAKUMAR, Poorani; LAI, Gabrielle; O'BRIEN, Beth Ann; ONG, Quan He
Abstract: To code-switch or not to code-switch? This is a dilemma for many bilingual language teachers. In this study, the influence of teachers' CS on bilingual children's language and cognitive development is explored within heritage language (HL) classes in Singapore. Specifically, the relationship between children's language output, vocabulary development, and cognitive flexibility to teachers' classroom CS behavior, is examined within 20 preschool HL classrooms (10 Mandarin, 6 Malay, and 4 Tamil). Teachers' and children's utterances were recorded, transcribed, and analyzed for CS frequency and type (i.e., inter-sentential, intra-sentential). 173 students were assessed with receptive vocabulary and dimensional card sort tasks, and their vocabulary and cognitive switching scores assessed using correlational and mixed effects analyses. Results show that inter-sentential and intra-sentential CS frequency is positively and significantly related to children's intra-sentential CS frequency. Overall, findings revealed that teachers code-switched habitually more often than for instructional purposes. Neither inter-sentential nor intra-sentential CS was significantly related to children's development in HL vocabulary, and intra-sentential CS was found to positively and significantly relate to children's growth in cognitive flexibility. These findings reveal the multi-faceted impact of teacher's CS on children's early development.